Exploring the Synergistic Anticancer Potential of Linagliptin and Esomeprazole in Cervical Cancer Cell Line: Mechanistic Insights into Targeting HSPB1, Hsp60 - Gaber Arean, Aiad; Elttayef Jasim, Maha; K. Awn, Anas; Yasin, Youssef Shakuri; Hamoody Jumaa, Azal (Asian Pacific Journal of Cancer Biology, 2025)
Objective: This study assessed the anticancer properties of the linagliptin-esomeprazole combination and investigated its molecular mechanism by analyzing its ability to target heat shock proteins. Methods: Over 24 and 72 hours, a HeLa cell line was used to assess the cytotoxicity of linagliptin, esomeprazole, the linagliptin-esomeprazole mixture, and cisplatin. The safety and selective toxicity of the mixture were evaluated using the human-derived adipose tissue cell line NHF. The concentrations of linagliptin, esomeprazole, cisplatin, and the mixture ranged from 0.1 to 1000 µg/ml. The study involved an estimated combination index value to assess the potential synergistic effect of linagliptin and esomeprazole. The dose reduction index was used to evaluate decreases in the cytotoxic concentrations of the mixture components, indicating the mixture’s safety and potency. The study uses computational molecular docking simulations to evaluate the binding affinity of linagliptin and esomeprazole to different cancer-related heat shock proteins. Results: Our study’s findings show that linagliptin, esomeprazole, and their combination inhibit the growth of cervical cancer cells, with the mixture being more cytotoxic than either individual drug and cisplatin. The interaction between linagliptin and esomeprazole demonstrated synergistic cytotoxicity, as the combination index score indicated. The mixture displayed selective toxicity toward cancer cells, suggesting a lower risk of adverse effects, supported by the selective toxicity and dose reduction indexes. The pilot study of computational molecular docking simulations involving various Heat shock proteins showed optimal interactions of linagliptin and esomeprazole with HSPB1 and Hsp60, respectively, with docking scores of -8.8 kcal/mol and -7.6 kcal/mol. Conclusion: The findings from our study, including the MTT assay, combination index, dose reduction index, selective toxicity index, and computational docking simulations, indicate that the linagliptin–esomeprazole mixture is a promising, effective, safer, and cost-efficient alternative to traditional chemotherapy for cervical cancer.